Exergame for post-stroke rehabilitation among elderly patients: A systematic review and meta-analysis - Teuku F. Duta; Ghina Tsurayya; Muhammad A. Naufal (Narra X, 2023)
Advancement in gaming technology, including exergame, is thought to offer a promising innovation in rehabilitative treatment owing to its interactive and joyful natures. Elderly, in addition to being prevalent in stroke, they have different perspectives and adaptability toward the utilization of exergame in post-stroke rehabilitation. The aim of this study was to evaluate the effectiveness of exergame-based rehabilitation in ameliorating stroke-associated cognitive impairment among elderly patients. This systematic review followed the Preferred Reporting Item for Systematic Review and Meta-Analysis (PRISMA) guideline. The literatures were retrieved from the searches on PubMed, Scopus, and Embase databases using a combination of ‘exergame’, ‘stroke’, and ‘elderly’ along with their respective synonyms. Included studies were controlled observational studies and randomized clinical trials with subjects’ mean age >60 years old, measuring global cognitive and/or five cognitive domains (attention, language, executive function, memory, and visuospatial ability). Quality appraisals were performed based on the Cochrane ‘risk-of-bias tool’ and Physiotherapy Evidence Database Scale. Studies with high and good qualities were included in the meta-analyses. Six randomized controlled trials involving 179 patients were included in meta-analysis. Studies had variations in terms of type (combination of exergame-based and conventional rehabilitation or exergame-based only) and duration of interventions (30–110 min), length of observation (2–6 weeks), and tools used to examine cognitive outcomes. As compared with conventional rehabilitation, exergame-based rehabilitation was significantly more effective to improve global cognitive based on Montreal Cognitive Assessment Score in acute stroke patients (n=4; mean difference (MD) 3.66; 95% confidence interval (95%CI): 2.08, 5.24; p<0.00001), but significantly less effective in chronic stroke patients (n=2; MD -1.54; 95%CI: -2.28, -0.81; p<0.0001). In conclusion, global cognitive of elderly patients with acute strokes could be improved through exergame-based rehabilitation which is more effective as compared with conventional therapy.